Validation of empirical equations for determining the suitability of the territory for the setting of cemeteries – Implications for worldwide application - Miguel Falconí-Vélez; Tania Crisanto-Perrazo; Wendy Cachaguay Viracucha; Silvana Suntaxi Pachacama; Jonathan Guayasamín-Vergara; Arianna García-Bazurto; Theofilos Toulkeridis (Heliyon)
The final disposal of corpses is one of the activities that generates the greatest pollution. Chemicals, embalming fluids, greenhouse gas emissions, and other factors trigger contamination of soils and water sources in towns near cemeteries. This study aimed to validate empirical environmental equations to determine the suitability of territories for cemetery location in several cantons of Central Ecuador, address study variables measured in the field, and update the bibliography as a rapid decision-making tool for decentralized governments. To achieve this objective, we used various determined variables, such as the phreatic level and slope in the field, and evaluated other variables and values, including the distance to water sources, precipitation, soil type, cemetery age, temperature, number of graves, geological faults, and population density, for 15 cemeteries. The resulting values were used in 135 equations to determine the territorial suitability of the cemetery locations. The outcomes allowed the equations to be segmented into three groups: those that coincided with the initial theoretical category assigned to the reference studies; those that had a higher or lower category than the original studies; and those that did not coincide with the original studies. Despite their limitations, the equations developed in this study may provide a fast and inexpensive solution to define the construction setting of cemeteries worldwide. Furthermore, the results can be used for norms and standards in local territorial planning plans while using strict initial categorization controls.